LAW ENFORCEMENT AGAINST CORRUPTION IN THE CHARITY OF WATER SUPPLY PROGRAM IN BITUNG - Sitepu, Anak Agung Gede Wibowo; Amiq, Bahrul; Prawesthi, Wahyu (Srawung: Journal of Social Sciences and Humanities, 2023)
Corruption is a crime that not only causing financial losses to country, but also violating social and economic rights of the community. The unlawful act of corruption is not only committed by state officials and between states, but also by state officials and other parties such as families and businessmen. This research aims to identify the law enforcement against perpetrators of corruption in Bitung regarding charity of water supply program activities based on Decision Number 20/Pid.Sus-TPK/2022/PN.Mnd. The method used in this research is juridical sociological approach, that uses legal aspects (legislation and reality) concerning the research topic. This approach is related to examining the positive law of the research object and observing the practice directly in the field. The research findings revealed that regional financial losses of IDR 14,000,000,000 were caused as the results of the unlawful acts of corruption and abuse of authority comitted by Raymond Richard Jotham Luntungan and Mohammad Nurcholis Laminula, who both were in charge of Charity of Water Supply Program for Low-Income Communities at Bitung during 2017-2018.